Vision 2030 Jamaica national development plan (Vision 2030 Jamaica Secretariat Kingston 5JM, 2009)
Presents a strategic guide or roadmap for Jamaica which aims to achieve developed country status by 2030.
Keywords: DEVELOPMENT PLANS